Kemampuan pemahaman membaca teks dan komunikasi matematik sebagai landasan dalam pemecahan masalah - Neneng Maryani (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This article is a review of international research articles that specifically emphasize the discussion of the ability to read mathematical texts and communicate mathematics as a basis for problem solving. The detailed descriptions include the criteria for understanding in reading a mathematical text; the effectiveness of language-based programs in school mathematics on student understanding; the use of learning approaches and media in building conceptual understanding and communication in solving mathematical problems; and strategies to build mathematical communication.